THE USE OF LEARNING MANAGEMENT SYSTEM (LMS) IN THE TEACHING AND LEARNING PROCESS : LITERATURE REVIEW - Irfandi Irfandi; Festiyed Festiyed; Yerimadesi Yerimadesi; Teguh Febri Sudarma (Jurnal Pendidikan Fisika, 2023)
Learning Management System or also called LMS as it is also known, can be considered as a type of online content management or online content delivery platform. It is used to deliver training and educational materials to the workforce or external users via the Internet. Based on that, this article aims to identify and analyze publications about online learning or online learning (in networks) with research data taken from journal articles starting in 2018-2022 as many as 124 articles from both national and international journals. The stages of data analysis consisted of searching journals through Google Scholar and also through the Mendeley application, checking the completeness of articles, mapping articles, conducting Literature Review analysis in addition to seeing the mapping and relationships between articles and seeing their distribution with bibliometric analysis with VOSviewer and making conclusions. Research on the development of the Learning Management System (LMS) Publication in 2018-2022 experienced significant developments in 2021 where the Covid pandemic occurred in early 2020 and the use of LMS was mostly dominated by universities or higher levels education. Where the university has preparedness in various aspects including human resources, qualified facilities and technology users are students who understand technology.